Experimental study of crack initiation angle in PMMA and PS plates under mixed-mode loading - Işık, A. Cenk. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
The purpose of this study is to determine crack initiation angles, the effect of critical radius and T-stress on crack initiation angles using experimental and analytical techniques. The results obtained using the maximum tangential stress (MTS-criterion), the generalized maximum tangential stress (GMTS-criterion), the minimum strain energy density (S-criterion) and the maximum triaxial stress (M-criterion) criteria are compared to experimental results of PMMA and PS specimens with an inclined center crack, under mixed-mode loading.
Keywords: Polymethylmethacrylate.; Materials -- Cracking.; Fracture mechanics.